ISAC constant modulus waveform design based on multi-target fair sensing - SHI Mingli; LI Xiaohui; LYU Siting (Tongxin xuebao)
To communicate and sense simultaneously in the integrated sensing and communication system, for the fair sensing of multiple targets and the error-free transmission of multi-user symbols, a ISAC constant modulus waveform design based on multi-target fair sensing was proposed. Considering the error free transmission of multi-user data symbols and the constant modulus constraint of waveform, an integrated sensing and communication waveform design model with joint waveform and signal scaling factor optimization was formulated. By using an alternate optimization algorithm, the coupling of waveform and signal scaling factor variables in constraint conditions was decoupled. The convex upper bounds of the non-convex expression of target illumination power and received echo SNR in the original sub-problem were obtained by the majorization-minimization algorithm, and then the constant modulus constraints for transmitted waveform was dealt with by the alternating direction method of multipliers algorithm. The simulation results show that compared with the waveform design method which maximizes the total target illumination power and the SNR of echo, the proposed waveform design method based on maximizing the minimum target illumination power only has a 3 dB performance loss of echo SNR. However, it can achieve better multi-target sensing fairness and realize error-free transmission of communication data symbols.